2017
DOI: 10.1186/s12913-017-2077-7
|View full text |Cite
|
Sign up to set email alerts
|

The Alice Springs Hospital Readmission Prevention Project (ASHRAPP): a randomised control trial

Abstract: BackgroundHospitals are frequently faced with high levels of emergency department presentations and demand for inpatient care. An important contributing factor is the subset of patients with complex chronic diseases who have frequent and preventable exacerbations of their chronic diseases. Evidence suggests that some of these hospital readmissions can be prevented with appropriate transitional care. Whilst there is a growing body of evidence for transitional care processes in urban, non-indigenous settings, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
0
18
0
8
Order By: Relevance
“…Rising health care costs stemming from increased prevalence of chronic diseases, lengthy hospitalizations, and hospital readmissions have shifted the paradigm from in-hospital care to caring for clients in the home. 1,2 Cost containment strategies shifting care to the home have highlighted a vital role for home health care in reducing readmission rates and improving outcomes. [3][4][5] This important shift to care for clients in the home has increased demand for home health services and subsequently has led to an overwhelming need for home health care workers (HHCWs).…”
Section: Introductionmentioning
confidence: 99%
“…Rising health care costs stemming from increased prevalence of chronic diseases, lengthy hospitalizations, and hospital readmissions have shifted the paradigm from in-hospital care to caring for clients in the home. 1,2 Cost containment strategies shifting care to the home have highlighted a vital role for home health care in reducing readmission rates and improving outcomes. [3][4][5] This important shift to care for clients in the home has increased demand for home health services and subsequently has led to an overwhelming need for home health care workers (HHCWs).…”
Section: Introductionmentioning
confidence: 99%
“…This is usually because the patient does not receive adequate support from family, social environment and primary health care. Readmissions of these patients can be reduced by good care at home or with good protection (22).…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives aimed at reducing admission to hospital can reduce the crowd in the emergency room, improve patient outcomes, and contribute positively to existing hospital facilities without requiring an additional cost and additional hospital beds. It was found that a comprehensive good discharge planning and temporary care were effective in reducing readmission to the hospital and facilitated follow-up with primary health care after discharge from the hospital (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that good transitional care is an important factor in preventing ED visits and readmission to the hospital. 12 Many of our patients are operated on in an ambulatory surgical center setting, where they receive a written postoperative instruction sheet prior to discharge. The instruction sheet includes a phone number to call for any questions or concerns.…”
Section: Discussionmentioning
confidence: 99%